PENGELOLAAN BANK SAMPAH SEBAGAI PENGEMBANGAN KARAKTER PEDULI LINGKUNGAN (Studi Bank Sampah Kumala Tanjung Priok) - Cendra Hardiyanto; Damanhuri Damanhuri; Febrian Alwan Bahrudin (Genta Mulia : Jurnal Ilmiah Pendidikan, 2022)
AbstractThe study aims to describe how Kumala’s waste bank management as an ecological character development. The subject of this study is the management of the Kumala garbage banks, and the surrounding communities. The study uses a qualitative approach with a descriptive method. The data-collection techniques that are done are interviews, observations, and documentation. The data analysis used is the collecting of data, the reduction of data, the presentation of data and the drawing of conclusions. The validity of data made by testing credibility and engineering triangulation. Research found that the management of garbage done by 3R (Reduce, Reuse and Recyle) that was later developed to 5R (Reduce, Reuse, Recyle, Resale and Reshare). Ecological character development through recycling and crafting activities. The barriers to waste management and environmental character development of education, knowledge, perception, income, goverment/public character roles, and infrastructure tools. Environmental character development solutions include education about waste banks and the importance of keeping the ward clean. Keywords: Waste Management, Bank Trash, and Environmental Character.